2020
DOI: 10.1177/0309133320932880
|View full text |Cite|
|
Sign up to set email alerts
|

Controls on dune scarping

Abstract: The controls that affect the degree of spatio-temporal change to foredunes following scarping are reviewed herein. As sea-levels rises and climate changes, dune scarping will become more common. Thus, it is critical to understand what factors contribute to the magnitude of scarping, and what effect this has on dune systems to better manage coastal erosion into the future. Scarping occurs when foredunes are partially eroded by waves, generally during periods of high water level. The controls on the degree and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 137 publications
(250 reference statements)
0
41
0
Order By: Relevance
“…The dune toe is a key parameter to describe the dune profile and is part of the spatially and temporally varying beach-dune system typically moving seawards during accretionary periods, and landwards during storms and erosion events 10 13 . With SLR, the vertical extent of marine processes is altered, which influences the sediment budget of sandy beaches.…”
Section: Introductionmentioning
confidence: 99%
“…The dune toe is a key parameter to describe the dune profile and is part of the spatially and temporally varying beach-dune system typically moving seawards during accretionary periods, and landwards during storms and erosion events 10 13 . With SLR, the vertical extent of marine processes is altered, which influences the sediment budget of sandy beaches.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, forecasts and assessments are performed on individual profiles because the intensity of large-scale erosion is not only associated with the offshore characteristics of a storm event such as the maximum storm surge, maximum wave height and duration, but also on pre-storm dune and foreshore morphology and their interactions with the forcing (Houser et al, 2008;Masselink et al, 2016;Athanasiou et al, 2018;Davidson et al, 2020). Exploration and understanding of these dependencies require the availability of high-quality observations of coastal change with pre-and post-storm surveys over large coastal areas, which are quite challenging to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on the geomorphic effects of sand fencing, Itzkin et al (2020a) demonstrated that foredunes are lower in elevation in areas where sand fences are constructed but that the dune system overall is substantially wider than foredunes in areas without sand fences. Other management actions, such as allowing vehicles to drive on beaches and beach raking, can also generate trade-offs between dune growth and coastal protection (Defeo et al, 2009). In a study on the effects of dune grass removal to restore Western snowy plover habitats in the PNW, Biel et al (2017) used XBeach (Roelvink et al, 2009) to explore dune erosion and found that where beachgrasses were removed, dunes maintained a lower elevation and were predicted to be more vulnerable to erosion compared to foredunes where beachgrasses were not removed and grew to a stable elevation.…”
Section: Introductionmentioning
confidence: 99%